1990
DOI: 10.1002/ajmg.1320350321
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise oligogenic segregation and linkage analysis illustrated with dopamine‐β‐hydroxylase activity

Abstract: A stepwise oligogenic method is developed that can be used to adjust the phenotype of a quantitative trait for the effects of a previously identified single-locus component. This method assumes that a single-locus component can be adequately identified through the use of segregation and/or linkage analysis under a 1-locus model and that the variation due to that locus can be removed from the phenotype leaving a residual that can be parameterized in terms of an additional single-locus component. Segregation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Abbreviations: tyr, tyrosine; TH, tyrosine hydroxylase; AADC, aromatic L-amino acid decarboxylase Building on the early work of Elston et al (1979), Goldin et al (1982) reported positive evidence for linkage between a locus influencing plasma DβH activity and the blood-group locus ABO. This observation was confirmed and extended by Elston et al (Asamoah et al 1987;Wilson et al 1988Wilson et al , 1990, who reported a maximum lod score >5.0 between ABO and plasma DβH activity. Simultaneously, Lamouroux et al (1987) cloned the cDNA encoding DβH protein, permitting molecular mapping by fluorescent in situ hybridization (Craig et al 1988), and molecular linkage studies (Gelernter et al 1991;Perry et al 1991).…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Abbreviations: tyr, tyrosine; TH, tyrosine hydroxylase; AADC, aromatic L-amino acid decarboxylase Building on the early work of Elston et al (1979), Goldin et al (1982) reported positive evidence for linkage between a locus influencing plasma DβH activity and the blood-group locus ABO. This observation was confirmed and extended by Elston et al (Asamoah et al 1987;Wilson et al 1988Wilson et al , 1990, who reported a maximum lod score >5.0 between ABO and plasma DβH activity. Simultaneously, Lamouroux et al (1987) cloned the cDNA encoding DβH protein, permitting molecular mapping by fluorescent in situ hybridization (Craig et al 1988), and molecular linkage studies (Gelernter et al 1991;Perry et al 1991).…”
supporting
confidence: 80%
“…In other words, determination of genotypes at −1021C→T can factor out up to 50% of the inter-individual variance in plasma DβH. The residual variance presumably reflects a combination of other loci influencing plasma DβH (Wilson et al 1988(Wilson et al , 1990Province 2000), and environmental or physiological influences on the measure. The plethora of inconclusive studies of plasma DβH, published largely in the 1970's and 1980's, thus bears re-examination in genotypecontrolled studies.…”
Section: Genotype-controlled Analysis Of Plasma Dβh In Alcohol Dependmentioning
confidence: 97%
“…It is still possible that an as yet unidentified DBH gene or a member of a related gene family in another chromosomal region is responsible for dystonia in these latter families. Recent work (Wilson et al 1990) suggests that there may be a second locus involved in determining levels of plasma DBH activity. Molecular genetic analysis has thus excluded a role for the known DBH gene on 9q34 in multiple forms of hereditary dystonia and revealed that there must be at least two autosomal loci that can produce a primary dystonic syndrome.…”
Section: Discussionmentioning
confidence: 98%
“…Because normal probability densities are used to model the genotypic distributions in quantitative linkage analysis, and these densities asymptotically approach, but never reach, zero in both tails, every individual has a non-zero probability for having each genotype. This is problematic when trying to identify recombination events that help to localize candidate regions, but methods have been developed to classify individuals based on their most probable genotype [27] .…”
Section: Brief Overview and History Of Linkage Analysismentioning
confidence: 99%
“…Many types of trait models can be used with this algorithm. These are outside the scope of this overview, but comprehensive reviews are available in several articles and texts [27,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] . Ott [65] implemented the Elston-Stewart algorithm to calculate the likelihood ratio test for linkage in human families of arbitrary size in LIPED, the first widely available computer program for this purpose.…”
Section: Brief Overview and History Of Linkage Analysismentioning
confidence: 99%